TENDENCIES OF DEVELOPMENT OF NETWORK MANAGEMENT MECHANISM IN THE ELECTRONIC ENVIRONMENT ORGANIZATION - Natalya Krivorotova (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the current trends in the external business environment the organization in terms of electronic-communications network and the impact of its changes to transform the organization's management system. Tendencies of changes in the external business environment the organization in terms of electronic-communications network, the impact of its changes to the transformation of the organization's management system and identified the possibilities and limitations of electron- networking tools provide communication links.